2012
DOI: 10.1029/2012ja018031
|View full text |Cite
|
Sign up to set email alerts
|

Gyroresonant interactions between the radiation belt electrons and whistler mode chorus waves in the radiation environments of Earth, Jupiter, and Saturn: A comparative study

Abstract: [1] In the current study we perform a comparative analysis of the gyroresonant interactions of whistler mode waves with radiation belt electrons in the magnetospheres of Earth, Jupiter, and Saturn. Our primary goal is to evaluate the effect of resonant wave-particle interactions with chorus waves and determine whether chorus waves can produce net acceleration or net loss of radiation belt electrons on the outer planets. The ratio of plasma frequency to gyrofrequency is a key parameter that determines the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 81 publications
8
102
0
Order By: Relevance
“…In reality the initial conditions may already include acceleration and loss due to cyclotron-resonant interactions with chorus and other waves, but at present this contribution cannot be separated out of the observations. A useful discussion of this effect can be found in Shprits et al (2012). A dipole magnetic field was used in the model, which is a reasonable assumption for distances up to approximately 14 R J along the equator.…”
Section: Evolution Of Electron Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality the initial conditions may already include acceleration and loss due to cyclotron-resonant interactions with chorus and other waves, but at present this contribution cannot be separated out of the observations. A useful discussion of this effect can be found in Shprits et al (2012). A dipole magnetic field was used in the model, which is a reasonable assumption for distances up to approximately 14 R J along the equator.…”
Section: Evolution Of Electron Fluxmentioning
confidence: 99%
“…Since the plasma density drops significantly with increasing latitude (Bagenal, 1994), the conditions for acceleration may be more favorable at higher latitudes. Shprits et al (2012) showed that changing the theoretical latitudinal extent of the chorus waves plays a major role in the effectiveness of wave-particle interactions at Jupiter and Saturn. In this study we use data from the Galileo spacecraft to investigate in more detail the acceleration of electrons by wave-particle interactions at Jupiter in the region outside Io.…”
Section: Introductionmentioning
confidence: 99%
“…37,40,42,58,64,67 Multiple spacecraft observations of intense emissions of parallel (relative to the background magnetic field) whistler-mode waves during geomagnetic storms and substorms 1,33,38 have led to the suggestion that these parallel waves could be responsible for almost all the recorded variations of electron fluxes. In addition, oblique wave damping due to Landau resonance with a dense population of suprathermal electrons 20,36 often sensibly decreases the amplitudes of oblique whistler-mode waves along their propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial life requires liquid water. The stability of liquid water at the surface of a planet defines a habitable zone around a star (see e.g., Dole 1964;Shklovskii and Sagan 1966;Huang 1959Huang , 1961Hart 1980). In the solar system, it stretches between Venus and Mars, but excludes these two planets.…”
Section: Habitabilitymentioning
confidence: 99%